Synthesis and characterization of the biodegradable copolymers from succinic acid and adipic acid with 1,4-butanediol - Ahn, BD; Kim, SH; Kim, YH; Yang, JS (JOHN WILEY & SONS INC, 2001)
Biodegradable homopolyesters such as poly(butylene succinate) (PBSU) and poly(butylene adipate) (PBAD) and copolyesters such as poly(butylene succinate-co-butylene adipate) (PBSA) were synthesized, respectively, from succinic acid (SA) and adipic acid (AA) with 1,4-butanediol through a two-step process of esterification and deglycolization. The polyester compositions and physical properties of both homopolyesters and copolyesters were investigated by H-1- and C-13-NMR, DSC, GPC, WAY-D, and optical polarizing microscopy. The melting point (T-m) of these copolyesters decreased gradually as the contents of butylene adipate increased and the glass-transition temperature (T-g) of these copolyesters decreased linearly as the contents of the adipoyl unit increased. PBSA copolyesters showed two types of XRD patterns of PBSU and PBAD homopolyesters. Furthermore, the biodegradation and hydrolytic degradation of the high molecular weight PBSU homopolyester, PBAD homopolyester, and PBSA copolyesters were investigated in the composting soil and NH4Cl aqueous solutions at a pH level of 10.6. (C) 2001 John Wiley & Sons, Inc.
Keywords: MULTIPLE MELTING ENDOTHERMS; ALIPHATIC POLYESTERS; STANNOUS OCTOATE; MORPHOLOGY; POLYMERS; COPOLYESTERS; DEGRADATION; POLYESTERIFICATION; TEREPHTHALATE; POLYETHYLENE